Element-ligand cooperativity with p-block Elements - Greb, Lutz; Ebner, Fabian; Ginzburg, Yael; Sigmund, Lukas M. (European journal of inorganic chemistry, 2020)
Metal-ligand cooperativity (MLC) had a tremendous impact on d-block metal-mediated bond activation and homogeneous catalysis. Is this concept translatable to the elements of the p-block? Are there analogies already at hand? In this review, we describe contributions in which a p-block element (group 13-15) and its ligand (surrounding molecular framework) operate synergistically in a substrate activation or a catalytic cycle. This activity is termed element-ligand cooperativity (ELC), in correspondence to MLC. After the concepts of p-block low-valent states and frustrated Lewis pairs mimicking the ambiphilic reactivity of transition metals, the spatial proximity of nucleophilic and electrophilic reaction sites and a small HOMO-LUMO gap in a p-block ELC complex might offer yet another approach. Selected examples shall illustrate common reactivities of ELC, disclose conceptual analogies with d-block MLC, and outline shortcomings in this field.